(untitled) (Al-Qamar, 2021)
A majority of western scholars have targeted the polices and treaties of Prophet Muhammad with Jews of Medina. This paper compares a number of historical information about the Prophet Muhammad relationship with Jews presented by W. Montgomery Watt and Robert Spencer in their Quran Commentaries. The study adopts qualitative and descriptive research method. For this purpose, explanatory notes of both scholars about the different verses of Quran on the present topic were selected, analyzed and compared in the light of Quranic sciences of Tafsir. The research shows that Prophet Muhammad’s teachings and actions uphold human values ​​and tolerance. The Prophet Muhammad never imposed anybody to become Muslim at that time. This paper rejects views and hostile blames of both western scholars. This paper also describes the context of the Prophet Muhammad treatment with Jews of Medina. While Prophet Muhammad has been criticized for taking advantage of this power and being violent, this article argues otherwise. Through the examples provided, it becomes evident that Prophet Muhammad preferred peace first and foremost at all times.